Study of partogram in relation to labour outcome and significance of alert line in partogram - Ghanghoriya, Vineeta; Patel, Kirti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The partogram is a simple, inexpensive tool to provide a continuous pictorial overview of labor. The goal of this study is to use partograph to monitor labor, initiate uterine activity that is sufficient to produce cervical changes, fetal descent while avoiding uterine hyperstimulation, hypostimulation and fetal distress and provide timely surgical intervention where required. Methods: Total 200 term patients, both primigravida and multigravida were selected for study and partograph recording were commenced at 4 cm dilation close maternal and fetal monitoring was done throughout the labour and partogram was plotted to detect any deviation from normal course. Results: Patients were grouped into primigravida and multigravida and based on partogram finding divided into delivered “before alert line” and “between alert and action line” and after action line.175 women delivered vaginally, out of this 106 delivered before alert line ,83 between alert line and action line and 11 after crossing action line. Conclusions: Partographic management of labour is a time honored and evidence based scientific way of managing labour. Partograph improves the quality of delivery care, since it permits to identify dystocia and make logical and effective interventions. It reduces unnecessary strain on mothers by reducing total duration of labour, without any increased foetal morbidity and mortality.